Evaluation of the specific effects of intranasal glucagon on glucose production and lipid concentration in healthy men during a pancreatic clamp. Issue 2 (14th September 2017) - Dash, Satya; Xiao, Changting; Stahel, Priska; Koulajian, Khajag; Giacca, Adria; Lewis, Gary F.
Abstract : Aim: To investigate the specific effects of intranasal glucagon (ING) on plasma glucose, endogenous glucose production (EGP) and lipid concentration. Methods: We conducted a single‐blind, randomized, crossover study at our academic investigation unit. Under pancreatic clamp conditions with tracer infusion, 1 mg ING or intranasal placebo (INP) was administered to 10 healthy men. As pilot studies showed that ING transiently increased plasma glucagon, we infused intravenous glucagon for 30 minutes along with INP to ensure similar plasma glucagon concentrations between interventions. The main outcome measures were plasma glucose, EGP, free fatty acid (FFA) and triglyceride (TG) concentrations. Results: In the presence of similar plasma glucagon concentrations, the increase in plasma glucose under these experimental conditions was attenuated with ING (mean plasma glucose analysis of variance P  < .001) with reduction in EGP ( P  = .027). No significant differences were seen in plasma FFA and TG concentrations. Conclusion: ING raises plasma glucose but this route of administration attenuates the gluco‐stimulatory effect of glucagon by reducing EGP. This observation invites speculation about a potential central nervous system effect of glucagon, which requires further investigation. If ING is developed as a treatment for hypoglycaemia, this attenuated effect on plasma glucose should be taken into account.